Effect of Laminaria japonica Powder on Physicochemical Properties, Rheological Properties and Protein Structure of Silver Carp Surimi Gel - Fengchao ZHOU; Wenting JIANG; Han TIAN; Wei LUO; Xiaolan ZHANG; Jiazhen WANG; Jie LIANG; Leiwen XIANG; Shaoyun WANG; Xixi CAI; Qiming WU; Honglai LIN (Shipin gongye ke-ji)
In order to improve the gel properties of surimi, the surimi gel was prepared by adding Laminaria japonica powder (LJP) with a mass fraction of 2%~10% in silver carp surimi. The effect of amount of LJP on the gel strength, texture, water holding capacity, rheological properties, chemical forces, myofibrillar protein (MP) secondary structure, color and microstructure of the surimr gel were analyzed. Thus, the intrinsic cause of LJP improving the surimi gel quality was explored. Results showed that the addition of LJP significantly improved (P<0.05) the gel strength, hardness and WHC of the surimi gels, these three indicators were increased first and then decreased later with the increased of LJP addition (highest at 8% added). When the addition amount was 10%, the gel strength, hardness and WHC indicators of the surimi gels significantly decrease (P<0.05). The LJP also had a significant improvement effects on the viscosity, stability and storage modulus (G') of the surimi sol, which promoted the formation of elastic gel, but the high amount of LJP (10%) added had a certain negative effect on the elastic gel. The polysaccharides enriched in LJP could formed polysaccharide-MP interaction with MP in surimi, which significantly increased hydrogen bond and ionic bond force in surini gel, and promoted the MP secondary structure transition to β-sheet, thus formed a surimi gel with small pore size and more dense structure. In conclusion, the appropriate amount of LJP added (6%~8%) can improve the quality of the surimi gel by affecting the gel characteristics, gel chemical forces and MP secondary structure.